2020
DOI: 10.21203/rs.3.rs-52921/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical and Radiographic Outcomes of Vital Inflamed Pulp Therapy in Immature Permanent Teeth with Irreversible Pulpitis: A Retrospective Case Series

Abstract: Background To assess the resolution of clinical symptoms and radiographic changes in root length and apical diameter in immature permanent teeth with irreversible pulpitis or apical periodontitis with vital inflamed pulp therapy (VIPT).Methods The faculty members at the Ninth People’s Hospital pediatric dentistry department were invited to submit consecutive VIPT cases treated by them, irrespective of outcome, between 2014 and 2016. Clinical success rate, radiographic changes in periapical radiolucency, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The mean increase in root length for MP was approximately 28% with an SD of approximately 16% according to the retrospective analysis of 13 cases collected from June 2015 to June 2016, 23 while the change rate for apexification was approximately 5% according to the published RCT research. 24 The Mann-Whitney-Wilcoxon test, based on Monte Carlo simulation in PASS 2019, was used to estimate the sample size.…”
Section: Methodsmentioning
confidence: 98%
“…The mean increase in root length for MP was approximately 28% with an SD of approximately 16% according to the retrospective analysis of 13 cases collected from June 2015 to June 2016, 23 while the change rate for apexification was approximately 5% according to the published RCT research. 24 The Mann-Whitney-Wilcoxon test, based on Monte Carlo simulation in PASS 2019, was used to estimate the sample size.…”
Section: Methodsmentioning
confidence: 98%
“…Therefore, it is very important for us to do our best to preserve these still vibrant dental pulp [9]. Besides, some case reports have shown that, in young permanent teeth, preserving these pulp tissues can promote the continued physiological development of roots already affected by apical periodontitis, a treatment approach known as IVPT [6,10]. Notably, this technique has heretofore been applied only to young permanent teeth.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is of utmost importance that we strive to preserve this viable dental pulp tissue instead of removing all dental pulp, like RCT [10]. Furthermore, several scholars have demonstrated that, in young permanent teeth, preserving pulp tissues can facilitate the ongoing physiological development of roots that have been compromised by apical periodontitis, an approach known as VIPT [6,11]. However, currently this treatment method is only limited to young permanent teeth.…”
Section: Introductionmentioning
confidence: 99%